Disaster Preparedness and Resiliency Among Vocational College Students in Hunan, China: A Quantitative Assessment - He, Jie (International Journal of Natural Resources and Environmental Studies, 2025)
This study examined the culture of preparedness and disaster resiliency among college students in a vocational college in Hunan Province, China. It aimed to assess students’ levels of disaster resilience and preparedness culture to inform the development of targeted interventions and educational programs that enhance safety and mitigate the impact of future disasters on this vulnerable population. The study involved 384 college students enrolled in a vocational college in Hunan Province. Data were collected using a self-constructed questionnaire specifically designed to address the study’s objectives. The findings revealed that the majority of respondents were young male students from Generation Z, aged 19 to 22, predominantly in their first year of study and majoring in Fire Protection Information and Security. Results indicated a generally positive culture of preparedness, characterized by shared awareness and understanding, proactive engagement, supportive environments, community building and resilience, and a commitment to continuous learning and improvement. Regarding disaster resiliency, students exhibited strong agreement across psychological, social, cognitive, and adaptability/resourcefulness domains. Significant differences were observed in both preparedness culture and disaster resiliency when grouped by age. However, no significant differences were found when grouped by sex. Analysis by academic year level revealed significant differences in preparedness culture, while both preparedness culture and disaster resiliency varied significantly when grouped by academic program or major. Based on the results, an action plan was proposed to enhance the culture of preparedness and disaster resiliency among vocational college students.